Pemanfaatan Platform Quizizz Sebagai Indikator Peningkatan Antusias Belajar Dan Kemampuan Pemahaman Konsep IPA - Muhammad Komarul Huda; Irwan Lihardo Hulu; Darma Al Doni (Mahesa Research Center, 2022)
This study aims to find out how much the Quizizz platform utilization as an indicator of increasing learning enthusiasm and ability to understand science concepts. The method used is descriptive quantitative. The research population is the seventh grade students of MTs. Al-Jihad Kerasaan as many as 5 classes with a total of 150 students. Determination of the sample using the Cluster Random Sampling technique (Random Class) with a sample of 30 students. The instrument to see the level of enthusiasm for learning is a checklist observation sheet filled out by an observer, while the instrument for understanding the level of science concepts uses a pre-test and post-test through the use of the Quizizz platform. Data analysis was carried out by calculating the average value of the pre-test and post-test for each meeting and calculating the average value of the percentage of students' enthusiasm for learning. The results showed an increase in student enthusiasm for learning by 25.6% and an increase in understanding science concepts as indicated by an increase in the post-test score of 14 points to 84.67 which had passed the KKM value for science subjects, which was 70. The results showed that the use of the Quizizz platform as an indicator of increasing enthusiasm for learning and the ability to understand science concepts is very large.